Propuesta urbana a través del análisis social del territorio en la Ciénaga la Bahía, del municipio de Soledad Atlántico 2024 (2024)
In the municipality of Soledad, department of Atlántico, there is the Ciénaga Bahía, located in the rural area of the municipality; in it, there are precarious settlements belonging to low-income groups, as mentioned in the results of UNESCO researchers in the article "Integrated development in human settlements in rural areas" (UNESCO, 2021). The Cienega Bahía de Soledad is an important ecosystem, an extensive area of mangroves and wetlands that harbors a great diversity of flora and fauna, including migratory birds and endangered species. This area plays a crucial role in protecting biodiversity and mitigating natural disasters such as floods and storms. It is also important for the local communities that depend on its natural resources for their livelihoods. Knowing the lack of sustainable resources in the national context and the current juncture between urban architecture and rural areas that have water sources and green spaces capable of being restored, it comes into question the anthropic activities for the preservation of the flora and fauna of the bay swamp in the municipality of Soledad; these human activities are developed over time and do not cease to be part of the daily life within the activities developed by man, such as agriculture, logging, livestock and other activities that work in the processes of pollution of water bodies and environment, in which, they are evidenced as the first place: exploitation of natural resources that drive us to the process of scientific research for the development of an environmental corridor, these environmental corridors become strategic areas that aim to connect one or more ecosystems that promote the conservation of flora and fauna within the territories and thus ensure better living conditions in the development of different species of animals and flora, ensuring a better welfare that contributes to these ecosystems to exist for a long time, counteracting anthropogenic activities given in the past or today. However, it is to be believed that the effective implementation of environmental corridors in Colombia faces challenges, such as the fragmentation of landscapes, which puts at risk of extinction some species typical of that habitat, this has always been considered as the main threat to conserve ecosystems, on the other hand, we find unsustainable human activities, such as overfishing and logging, both of which threaten to destroy habitats, and the lack of coordination between the different responsible entities. To overcome these problems, it is necessary to strengthen laws and norms within environmental governance, so that the different ecosystems can be taken advantage of, promote citizen participation and environmental awareness among the groups of residents that inhabit these types of ecosystems and thus help to conserve them in an optimal manner. On the other hand, in the middle of the project " Urban proposal through the social analysis of the territory in Ciénaga la Bahía, in the municipality of Soledad Atlántico 2024" are related: - Urban sustainability by implementing strategies to contribute to the creation of environmental protection spaces. - To the cultural extension and protection of the fauna and flora of the bay swamp. The implementation of strategies for environmental conservation through environmental corridors demonstrates the importance of conservation and recovery of the ecosystem and thus mitigate the negative impacts caused by the fragmentation of habitats. Therefore, the objective of the following work is: to propose a palafitic environmental corridor for the decrease of the environmental affectations and fragmentation of the ecosystem, generating new and more public spaces and green areas in the sector of the Cienega Bahía in the municipality of Soledad Atlántico. Therefore, it was considered to develop descriptive research with a participative action approach, and different stages were proposed: Characterize and delimit the area, supported by photographic records. Conduct studies by means of surveys. Organize working groups for the development of the research with the participation of the community. Conduct participatory workshops. News production by means of a flayer developed by the researchers themselves